Potent and broadly neutralizing antibodies against sarbecoviruses elicited by single ancestral SARS-CoV-2 infection - Lei Yu; Yajie Wang; Yuanchen Liu; Xiaomin Xing; Chen Li; Xun Wang; Jialu Shi; Wentai Ma; Jiayan Li; Yanjia Chen; Rui Qiao; Xiaoyu Zhao; et al. (Communications Biology)
Abstract The emergence of various SARS-CoV-2 variants presents challenges for antibody therapeutics, emphasizing the need for more potent and broadly neutralizing antibodies. Here, we employed an unbiased screening approach and successfully isolated two antibodies from individuals with only exposure to ancestral SARS-CoV-2. One of these antibodies, CYFN1006-1, exhibited robust cross-neutralization against a spectrum of SARS-CoV-2 variants, including the latest KP.2, KP.3 and XEC, with consistent IC50 values ranging from ~1 to 5 ng/mL. It also displayed broad neutralization activity against SARS-CoV and related sarbecoviruses. Structural analysis revealed that these antibodies target shared hotspot but mutation-resistant epitopes, with their Fabs locking receptor binding domains (RBDs) in the “down” conformation through interactions with adjacent Fabs and RBDs, and cross-linking Spike trimers into di-trimers. In vivo studies conducted in a JN.1-infected hamster model validated the protective efficacy of CYFN1006-1. These findings suggest that antibodies with cross-neutralization activities can be identified from individuals with exclusively ancestral virus exposure.